2017
DOI: 10.1111/scs.12445
|View full text |Cite
|
Sign up to set email alerts
|

Nursing professionals' experiences of the facilitators and barriers to the use of telehealth applications: a systematic review of qualitative studies

Abstract: The aim of the study was to synthesise the best available research evidence on nursing professionals' experiences of the facilitators and barriers to the use of online telehealth services in nursing practice. Telehealth is used to deliver healthcare services and health-related information by means of information and communication technology (ICT). The systematic review of qualitative studies was conducted using thematic synthesis of previous studies. International electronic databases PubMed, CINAHL, Eric, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
155
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(180 citation statements)
references
References 54 publications
16
155
1
8
Order By: Relevance
“…Murdoch et al () described the same situation. As stated by Koivunen and Saranto (), there is a need for the development of technological tools used in nursing practice. TN need to take part in such development to ensure that new technology is designed for their complex clinical reality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murdoch et al () described the same situation. As stated by Koivunen and Saranto (), there is a need for the development of technological tools used in nursing practice. TN need to take part in such development to ensure that new technology is designed for their complex clinical reality.…”
Section: Discussionmentioning
confidence: 99%
“…Active failures often occur due to insufficiency in the latent conditions (Reason, , ). A recent review by Koivunen and Saranto () concluded that healthcare organizations must assure that TN have enough support and resources and that there is a need for the development of technological tools in healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers concluded that managers had to refine policies to reflect benefits of IT in nursing practice. Further research also should be conducted to confirm patterns of nurses' adoption to IT in different contexts [2,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…With the new resources implanted in the health practice, the need for updating and qualification by the nurses to act and to provide a quality assistance is notorious. In addition to integrating health actions with the use of telehealth services, culminating in new and valuable technological alternatives that can overcome cultural, socioeconomic and geographical barriers (11) .…”
Section: Discussionmentioning
confidence: 99%
“…This consists of the transmission of cardiovascular parameters, examinations and/or clinical data of patients through the internet and technological tools. In the last ten years, revolutionary progress in telecardiology has been made through the association of ICT, including cell phones and cloud archiving (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%